School-Based Education for Landslide Disaster Preparedness: A Systematic Review of Learning Processes, Outcomes, and Influencing Factors - Fania Hafidza Dwitarachmi; Enok Maryani; Dina Siti Logayah (Abjadia : International Journal of Education, 2026)
Disaster education provides significant opportunities to enhance students’ preparedness for disaster risks, particularly through school-based landslide education programs. However, previous studies have mainly examined learning processes, preparedness outcomes, or influencing factors separately, leaving limited integrative evidence regarding school-based landslide preparedness education. Therefore, this study addresses three main questions concerning: (1) the implementation of learning processes in school-based landslide education, (2) students’ preparedness outcomes, and (3) factors influencing program effectiveness. This study employed a PRISMA-compliant systematic literature review using the Scopus and Google Scholar databases. Literature searches were conducted using keywords related to school-based education, disaster preparedness, landslides, and students, covering publications from 2015–2025. From 522 identified studies, 21 articles met the inclusion criteria after screening and eligibility assessment. The findings indicate that school-based education improves students’ understanding of landslide risks, preparedness attitudes, risk awareness, and disaster response behavior through contextual and experiential learning approaches. Integrative learning processes, including STEAM-D approaches, disaster simulations, and field-based activities, were found to enhance students’ engagement and contextual understanding of disaster risks. Program effectiveness is influenced by curriculum integration, teacher capacity, environmental awareness, policy support, and resource availability. Despite its strong potential, challenges remain, including limited learning materials and insufficient institutional support. This study is among the first PRISMA-based systematic literature reviews to integrate learning processes, preparedness outcomes, and influencing factors in school-based landslide education.